A Conceptual Paper: Islamic Corporate Governance and Earnings Management - Winarsih; Maya Indriastuti; Ahmad Hijri Alfian (Proceedings of Femfest International Conference on Economics, Management, and Business, 2024)
Earnings management is a theme that is still interesting to research today. This is because earnings management is able to provide an overview of managers' behavior in reporting their business activities in a certain period, namely the possibility of the emergence of certain motivations that encourage them to manage or to arrange the reported financial data. This study will examine the Islamic corporate governance of earnings management with a target sample consisting of 65 annual reports of Islamic banks in Indonesia from 2018 to 2022 and be analyze by using panel data regression analysis. This research contributes to the literature on earnings management practices by looking at the extent to which Islamic banks in Indonesia take their controlling market expectations and keeping stock prices high